2013
DOI: 10.1063/1.4816255
|View full text |Cite
|
Sign up to set email alerts
|

Remanence plots technique extended to exchange bias systems

Abstract: Efforts have been recently made to use remanence plots in exchange-bias studies. However, since the two remnant magnetizations of a biased loop may differ, this technique cannot be applied in its classical form. This work extends it to systems with shifted loops and shows that the number of distinct plots is significantly increased. The approach was probed on Co/IrMn exchange bias films. Possible discrepancies between experiment and theory are pointed out and discussed. The adaptation of the model presented he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…After that, when the sample is saturated in negative fields the alignment is P again [6,9]. In order to estimate some magnetic parameters from the curves, the derivatives of the descending and ascending branches of the loop were calculated [18][19][20] investigated NiFe/IrMn/Co trilayers grown on Ta or Cu seed layers and found that crystalline texture influences the trilayers' magnetic properties [22]. This way, as discussed above, the difference of the H C and H EB values for S Nb when compared to those for S Ta , obtained at 6 K, may be attributed to the degree of (200) preferred orientation of the IrMn layer in S Nb .…”
Section: Resultsmentioning
confidence: 99%
“…After that, when the sample is saturated in negative fields the alignment is P again [6,9]. In order to estimate some magnetic parameters from the curves, the derivatives of the descending and ascending branches of the loop were calculated [18][19][20] investigated NiFe/IrMn/Co trilayers grown on Ta or Cu seed layers and found that crystalline texture influences the trilayers' magnetic properties [22]. This way, as discussed above, the difference of the H C and H EB values for S Nb when compared to those for S Ta , obtained at 6 K, may be attributed to the degree of (200) preferred orientation of the IrMn layer in S Nb .…”
Section: Resultsmentioning
confidence: 99%
“…Parametric plots of the remagnetization remnance versus demagnetization remnance, commonly known as Henkel plots, previously have been used to explore interactions in a variety of magnetic systems [1,2,3,4]. They are typically compared to Wohlfarth's prediction [5] for DC, AC, and thermally demagnetized samples based on noninteracting particles with uniaxial anisotropy at zero temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research found that the Henkel plots for particulate media depended upon the zero magnetization state starting point for the remagetization remnance [6]. Following this, researchers developed several Preisach models including a classical Preisach model (PM), moving Priesach model (MPM), and complete moving hysteresis model (CMH) to include the effects of the initial zero magnetization state [1,3,4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques, and variants of them proposed by Bissell [5], are suitable for both nano-structured and bulk magnetic materials, being highly versatile for experimental studies. Henkel plots [2] have been applied for the description of magnetic interactions in magnetic data storage [6], studies of magnetic rocks [7], studies of superconductors, hard and soft magnets [8], studies of exchange bias systems [9], other studies providing insights on interactions that govern magnetization processes [10][11][12][13][14][15][16][17][18][19][20], or indicate negative interaction processes in systems where no dipolar interactions are present [21,22]. Given the similarities between the ferromagnetic and ferroelectric materials in that both systems display hysteresis, coercive fields, Curie temperature, and remanent states used in both cases for digital data storage, in this paper it is hypothesized that the equivalent magnetic remanent DCD and IRM curves could be measured for a ferroelectric system and renamed DC Depolarization (DCDP) and Isothermal Remanent Polarization (IRP), respectively.…”
Section: Introductionmentioning
confidence: 99%